2x-(1-x)=6

Simple and best practice solution for 2x-(1-x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(1-x)=6 equation:


Simplifying
2x + -1(1 + -1x) = 6
2x + (1 * -1 + -1x * -1) = 6
2x + (-1 + 1x) = 6

Reorder the terms:
-1 + 2x + 1x = 6

Combine like terms: 2x + 1x = 3x
-1 + 3x = 6

Solving
-1 + 3x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 3x = 6 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = 6 + 1
3x = 6 + 1

Combine like terms: 6 + 1 = 7
3x = 7

Divide each side by '3'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| -4=-(x+5) | | 7+n+1=5(1-n) | | 2.67x=-1x | | 7x-53=4 | | -2(x-3)=26 | | 10(-3)+21=X | | 38=9x-61 | | 2x^2-4-44-x^2=0 | | 0.375+5/8 | | 2(-3)-3=X | | 2+14z=9z-8 | | 8x+6+x=1+4x-20 | | 4x-3/5=2x-1/2 | | 2*-6-3=X | | 4x=3x-30 | | x/5+1-2x/10=x | | 2x/10+1-2x/10=x | | 8m-2m-6=3m+2m | | X/3=x/4-13 | | 2x-1x=10x | | 4(n+2)=8 | | 4x-6y=22 | | (4w+3)(1+w)=0 | | R=5g+5uforg | | 2x=11+6y | | 13x-27=3x-177 | | 4(7x+3)=54 | | x^2+9x+182=0 | | 48-4x=5x+22 | | 460=110+(x*8) | | 4x-115(x+2)-x= | | 2xln(5x)+x=0 |

Equations solver categories